GAMM Annual Meeting - Darmstadt 2012 Overview of the Sections (Proceedings in applied mathematics and mechanics, 2012)
Volume 12 (2012) of PAMM “Proceedings in Applied Mathematics and Mechanics” assembles the contributions to the 83nd Annual Meeting of the Gesellschaft für Angewandte Mathematik und Mechanik, held 26 – 30 March 2012 at Technische Universität Darmstadt, Germany. The contributions are grouped according to the minisymposia and sessions of the conference. Overview of the Sections Minisymposia Mathematics Ma 1 Preconditioning in optimization with PDE constraints Ma 2 High performance linear algebra on GPUs Ma 3 Crystals and defects Minisymposia Mechanics Me 1 Homogenization from submicro to micro scales Me 3 Modelling of phase transformations in solids Sections 1–24 1 Multi‐body dynamics 2 Biomechanics 3 Damage and fracture mechanics 4 Structural mechanics 5 Nonlinear oscillations 6 Material modelling in solid mechanics 7 Coupled problems 8 Multiscales and homogenization 9 Laminar flows and transition 10 Turbulence and reactive flows 11 Interfacial flows 12 Waves and acoustics 13 Flow control 14 Applied analysis 15 Applied stochastics 16 Optimization 17 Applied and numerical linear algebra 18 Numerical methods of differential equations 19 Optimization of differential equations 20 Dynamics and control 21 Mathematical image processing 22 Scientific computing 23 Applied operator theory Young Researchers' Minisymposia YR Ma1 Stochastic partial differential equations (SPDEs) and applications YR Ma2 Differential algebraic equations: theory, numerics and applications YR Me1 Structural optimization in view of robustness and sensitivity YR Me2 Advanced material modeling strategies at different scales with application to production processes YR Me3 Non‐standard discretization methods for multi‐physics